Pregnancies and obstetrical prognosis after oocyte donation in Turner Syndrome: A multicentric study. (July 2019) - Andre, Hélène; Pimentel, Céline; Veau, Ségolène; Domin-Bernhard, Mathilde; Letur-Konirsch, Hélène; Priou, Gérard; Eustache, Florence; Vorilhon, Solène; Delepine-Panisset, Béatrice; Fauque, Patricia; Scheffler, Florence; Benhaim, Annie; et al.
Abstract: Introduction: Turner syndrome is one of the most frequent chromosomal abnormalities in women, with a prevalence estimated to be 1 of 2500 live birth. Pregnancy in women with Turner syndrome is known to be at high risk, whether it is spontaneous or after oocyte donation, because of miscarriages and potential cardio-vascular complications which can be life-threatening. All of these patients should therefore be screened with a comprehensive cardio-vascular assessment before pregnancy, and have a close follow-up during and after pregnancy. Patients and methods: It is a retrospective study, conducted in 10 of the 27 French oocyte donation centers between 2012 and 2016, on all the patients presenting with Turner syndrome included in an oocyte donation program. Results: 151 embryo transfers were realized in 73 patients, resulting in 39 pregnancies. Among these pregnancies, 24 children were born healthy, 11 spontaneous miscarriages, 3 voluntary abortions, 1 extra-uterine pregnancy and 1 maternal death from non-cardio-vascular origin occurred. Pregnancies were complicated by gravid arterial hypertension in 28.2% of cases, preeclampsia in 10.3% of cases, and gestational diabetes in 7.7% of cases. Conclusion: This study bring out obstetrical complications of the same magnitude than the ones described in the literature. Lead over a period of 4 years, in 10 French oocyte donation centers, it doesn't reveal any cardio-vascular complications, conversely to other studies published before French and American recommendations. This study reinforces the usefulness of specific recommendations for the care of these particular patients.